A line outage study for prediction of static voltage collapse - Moghavvemi, M.; Omar, F.M. (IEEE, 1998)
A simple but useful technique is proposed to study steady-state line outage and hence voltage collapse of the system. Voltage collapse prediction can be performed through the study of line outages, though techniques for nodal-based prediction or critical-node identification are frequently proposed. Experimentally, it was proven that both line outage and system voltage collapse take place simultaneously. In fact, line outages can be treated as the secondary cause of voltage collapse. A scalar index called line-stability index for each line is calculated based on the power flow through the line. The line-stability index may have a value that varies from zero (no power flows through the line) to one (maximum power flows through the line). Any line exceeding the maximum limit of stability index (1.00) can cause system-wide voltage collapse. The proposed technique is tested on a six-bus standard test system, and encouraging results are observed. The results obtained indicate that the technique has the potential to be used as a tool for system monitoring and future load planning.